2002
DOI: 10.1080/13678860110053678
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions and design criteria for developing training reaction evaluations

Abstract: Although there is research on training program evaluation, there is little systematic research on the design, development and use of training reaction evaluations. In order to obtain meaningful information from a program evaluation, evaluation professionals must be rigorous in the design and development of all aspects of an evaluation study, including instrumentation. The purposes of the study were to classify the dimensions of information sought using reaction evaluations and to establish design criteria for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 24 publications
(37 reference statements)
0
26
0
2
Order By: Relevance
“…Questionnaire Items Prior research indicates that the reaction questions need to assess multiple ways of looking at the underlying perception of value of a training program (Lee & Pershing, 2002). Meta-analysis (Alliger et al, 1997), several structural analyses of instruments (Brown, 2005;Morgan & Casper, 2000), and a review of applied practices (Lee & Pershing, 2002) have demonstrated that the measurement of sentiments about training quality needs to assess multiple features of a program.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Questionnaire Items Prior research indicates that the reaction questions need to assess multiple ways of looking at the underlying perception of value of a training program (Lee & Pershing, 2002). Meta-analysis (Alliger et al, 1997), several structural analyses of instruments (Brown, 2005;Morgan & Casper, 2000), and a review of applied practices (Lee & Pershing, 2002) have demonstrated that the measurement of sentiments about training quality needs to assess multiple features of a program.…”
Section: Methodsmentioning
confidence: 99%
“…Meta-analysis (Alliger et al, 1997), several structural analyses of instruments (Brown, 2005;Morgan & Casper, 2000), and a review of applied practices (Lee & Pershing, 2002) have demonstrated that the measurement of sentiments about training quality needs to assess multiple features of a program. Consistent with the need to assess sentiments from a number of viewpoints, multiple items were used in this instrument to address different elements of a training program in this organization.…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that if the most prevalent level of evaluation is to become more useful for evaluators, instructors, and learners then design and content need to adhere to uniform and consistent standards. Similar findings were reported in an examination of reaction instruments used in corporate settings (Lee & Pershing, 2002). In a study of corporate elearning program evaluations simplistic evaluation measures were identified as the primary focus (MacPherson et al, 2004).…”
Section: Review Of the Hrd Literaturementioning
confidence: 99%
“…The researchers who have examined and proposed evaluation models use Kirkpatrick's model as a basis for their investigations. Some researchers have introduced new comprehensive models (Alvarez et al 2004; Holton, 1996; Kaufman & Watkins, 2000), others have focused on one of the levels such as reaction or return on investments (Lee & Pershing, 2002; Pershing & Pershing, 2001; Wang, et al 2002). One study was identified that provided a detailed analysis on learning or behavior (Dooley et al, 2004).…”
Section: Review Of the Hrd Literaturementioning
confidence: 99%
“…The third factor to training relates to the perceived efficiency of training. It relates to the organization and the mode of operation of the course and it refers to an evaluation about regarding the physical location and administration of the course [27]. We capture these arguments in our study hypothesis.…”
Section: Effects Of Future Orientation On Context Performancementioning
confidence: 99%